(untitled) (Journal of Interdisciplinary Insights, 2026)
The purpose of this study is to systematically assess how climate change affects global and Mongolian economic growth, productivity, and risks. The study utilized international secondary data sources such as the World Bank, Germanwatch’s Climate Risk Index (CRI), and Our World in Data, covering the period from 1990 to 2023, and conducted descriptive and comparative analyses. The results indicate that Mongolia is economically highly vulnerable to climate change, particularly affecting agriculture, food prices, inflation, and labor productivity. The main contribution of the study lies in linking climate indicators with macroeconomic outcomes, providing risk channels and directions that can be used for policymaking in Mongolia. Climate change poses physical, transferable, and resource risks to the economy. Policymakers around the world are placing significant emphasis on mitigating the impacts of climate change, promoting green technologies, and promoting finance. The article examines the economic impacts and risks of climate change in countries and in Mongolia.